2014
DOI: 10.1371/journal.pntd.0002698
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Cyclooctadepsipeptides and Aminophenylamidines against Larval, Immature and Mature Adult Stages of a Parasitologically Characterized Trichurosis Model in Mice

Abstract: BackgroundThe genus Trichuris includes parasites of major relevance in veterinary and human medicine. Despite serious economic losses and enormous impact on public health, treatment options against whipworms are very limited. Additionally, there is an obvious lack of appropriately characterized experimental infection models. Therefore, a detailed parasitological characterization of a Trichuris muris isolate was performed in C57BL/10 mice. Subsequently, the in vivo efficacies of the aminophenylamidines amidante… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 47 publications
1
17
0
1
Order By: Relevance
“…The parent compound, PF1022A, which is much cheaper than emodepside, has recently been compared with emodepside for treatment of Trichuris muris , as a model for the human whipworm ( T. trichiura ), which is the dose-limiting gastrointestinal nematode in humans and particularly problematic due to its long period of prepatency. Although emodepside was much more effective than PF1022A after intraperitoneal and subcutaneous application, only a small difference was detected after oral application ( Kulke et al, 2014 ). It was also shown to be able to eliminate all stages of T. muris including histotropic L1.…”
Section: Cyclooctadepsipeptides: Mode Of Actionmentioning
confidence: 99%
“…The parent compound, PF1022A, which is much cheaper than emodepside, has recently been compared with emodepside for treatment of Trichuris muris , as a model for the human whipworm ( T. trichiura ), which is the dose-limiting gastrointestinal nematode in humans and particularly problematic due to its long period of prepatency. Although emodepside was much more effective than PF1022A after intraperitoneal and subcutaneous application, only a small difference was detected after oral application ( Kulke et al, 2014 ). It was also shown to be able to eliminate all stages of T. muris including histotropic L1.…”
Section: Cyclooctadepsipeptides: Mode Of Actionmentioning
confidence: 99%
“…Little is known about tribendimidine DDIs. Several in vitro and in vivo studies using nematode models have suggested possible effects of interactions between tribendimidine and other antiparasitic compounds, including albendazole, levamisole, ivermectin, cyclooctadepsipeptide PF1022A, emodepside, and crystal proteins (22)(23)(24)(25). Whether drug effects were additive, synergistic, or antagonistic varied widely depending on the compound and the parasite and in some cases reversed between in vitro and in vivo models.…”
mentioning
confidence: 99%
“…The anthelmintic potential of PF1022A and emodepside has been reported in numerous in vitro and in vivo Source: Harder et al, 2003, p. 320. studies (Harder & von Samson-Himmelstjerna, 2001;Kulke et al, 2013a;Kulke et al, 2013b;Kulke et al, 2014;Zahner et al, 2001a;Zahner et al, 2001b). Interestingly, PF1022A and emodepside have a broad spectrum of activity against several nematode species including those that are resistant to benzimidazoles, levamisole and ivermectin (von Samson-Himmelstjerna et al, 2005).…”
Section: Macrocyclic Lactones (Mlsmentioning
confidence: 99%
“…emodepside can directly open these channels ( Kulke et al, 2014) and that emodepside action on this splice variant of the channel does not require the presence of additional receptors like the latrophilin receptors for an emodepside effect (Willson et al, 2004). It does not however, rule out a contribution of latrophilin receptors to the overall mode of action of emodepside in parasites as indicated by the interaction of Lat-1 and emodepside (Saeger et al, 2001).…”
Section: B30 Emodepsidementioning
confidence: 99%
See 1 more Smart Citation